Histamine therapeutic efficacy in metastatic melanoma : role of histamine H4 receptor agonists and opportunity for combination with radiation - Massari, Noelia A. (2017)
Fil: Massari, Noelia A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Laboratorio de Radioisotopos; Argentina